1217. Molecular Epidemiology of Pseudomonas aeruginosa in Latin America: Clinical Isolates From Respiratory Tract Infection. (4th December 2021) - Cardinal, Leandro; Marcelino, Cicera P; Okuma, Aline; Mizuno, Gustavo; Tuon, Felipe; Gales, Ana C; Gales, Ana C; Negra, Marina Della; Polis, Thales; Beirao, Elisa
Abstract: Background: Respiratory Tract Infection (RTI) caused by P. aeruginosa is a common infection among hospitalized patients, with increased levels of morbidity and mortality. This pathogen exhibits multiple resistance mechanisms to antibiotics. We analyzed the molecular epidemiology and activity of the main therapeutic options against P. aeruginosa isolated from RTI in Latin America (LATAM). Methods: Isolates were collected from 36 sites in 10 countries during 2017-2019. Non-duplicate samples were consecutively collected. MICs were determined by broth microdilution and interpreted by CLSI criteria. A subset of imipenem non-susceptible isolates was selected for characterization of carbapenemase encoding genes via multiplex PCR and DNA sequencing. β-lactamase genes encoding ESBLs, carbapenemases, and plasmid-mediated AmpCs were investigated. Results: A total of 2, 044 P. aeruginosa were collected from RTI. Overall C/T [87.8% susceptible (S)] was the most active antimicrobial tested against P. aeruginosa isolates followed by amikacin (85.8% S) and imipenem/relebactam (IMI/REL; 82.5% S). Other antimicrobials had less than 80% susceptibility. C/T remained the most active agent including activity against imipenem and piperacillin/tazobactam non-susceptible isolates (Figure 1). 583 imipenem non-susceptible P. aeruginosa were selected for molecular analysis (Table 1 ). Thirty (5, 1%) isolates were confirmed to be producers of serine-carbapenemases [GES-5 (6 isolates); KPC-2 (24 isolates)], while 83 (14.2%) were MBL producers. KPC-2 was found in Colombia (9), Chile (6), Puerto Rico (4), Guatemala (3), and Brazil (2). GES-5 was identified in Mexico (3), Argentina (2) and Brazil (1). VIM-2 was the most common MBL encoding gene identified. IMP variants were observed in Brazil (IMP-56, IMP-1), Ecuador (IMP-13), Mexico (IMP-18), Panama (IMP-18) and Puerto Rico (IMP-18). SPM-1 was only encountered in Brazil. The production of ESBLs was low in most LATAM countries, except for Guatemala (80%) (Figure 2 ). Figure 1. Activities of selected antimicrobial agents against 2, 044 P. aeruginosa isolated from respiratory tract infections in Latin America (2017 to 2019). TABLE 1. Molecular analysis of imipenem non-susceptible P. aeruginosa isolates in Latin America (LATAM) from Respiratory Tract Infection (N=583). Figure 2. Carbapenemases identified in 583 imipenem non-susceptible P. aeruginosa isolated from patients with respiratory tract Infections in Latin America (LATAM). Conclusion: CT, amikacin and IMI/REL showed good activity against RTI isolates and could represent effective treatment options for P. aeruginosa infections. The prevalence of carbapenemases-encoding genes varied geographically in LATAM. Disclosures: Leandro Cardinal, PharmD, PhD, MSD (Employee) Cicera P. Marcelino, n/a, MSD (Employee) Aline Okuma, n/a, MSD (Employee)MSD Brazil (Employee) Gustavo Mizuno, PharmD, Merck Sharp Dohme (Employee) Felipe Tuon, PhD, Merck Sharp Dohme Brazil (Scientific Research Study Investigator) Ana C. Gales, MD, MSD (Board Member, Advisor or Review Panel member, Speaker's Bureau)Pfizer (Board Member, Consultant, Advisor or Review Panel member, Speaker's Bureau) Marina Della Negra, Medical Doctor, MSD Brazil (Employee) Thales Polis, Medical Doctor, MSD Brazil (Employee)